Determinan yang Mempengaruhi Audit Delay pada Perusahaan Sub Sektor Proferti dan Real Estate di Bursa Efek Indonesia (BEI) Tahun 2019-2023 - Fillany, Ricken; Hambani, Susy; Anwar, Saeful (Innovative: Journal Of Social Science Research, 2024)
Companies that issue their shares on the stock market are required to submit annual reports; however, many businesses, primarily dominated by property companies, are delayed in publication due to audit postponements. The study aims to determine the influence of company size, profitability, solvency, and liquidity on audit delay and to identify the factor with the greatest impact. The results indicate that company size, profitability, solvency, and liquidity collectively have a significant effect on audit delay; however, company size and profitability do not have a significant partial effect on audit delay. On the other hand, solvency and liquidity significantly affect audit delay in companies within the property and real estate subsector. The most influential factor on audit delay is liquidity.